Tissue resident memory T cells (TRM) - Veldhoen, Marc (Henry Stewart Talks, 2022)
T cell activation, T cell response, T cell memory, Tissue Resident Memory T cells (TRM), TRM cell development, TRM cell transcription factors, TRM cell function, Aberrant TRM cell roles